Aerodynamic characteristics of compound wing configuration of wing-in-ground effect vehicle - Jamei, Saeed (2012)
Wing-in-ground effect (WIG) craft can be considered as a new technology for marine transportation. High speed performance of WIG craft has high advantage as compared to other marine transport designs. The performance of WIG craft depends mostly on its wing configurations. In this thesis, the aerodynamic characteristics of a new compound wing were numerically and experimentally investigated in proximity of the ground. The compound wing was divided into three parts where one rectangular wing in the middle and two reverse taper wings with anhedral angle at the sides. NACA6409 airfoil was selected as a case study for the wing airfoil section. Three dimensional (3D) computational fluid dynamics (CFD) was applied as a numerical model. The governing equations are the three-dimensional incompressible Navier–Stokes equations for continuity and momentum. Different turbulent models were used for the turbulent flow around the wing surface. For validation purpose, wind tunnel experiments were carried out, and other published experimental work were used for comparison, where the current numerical simulation result is found to have good agreement with them. The experiments carried out in Universiti Teknologi Malaysia low speed wind tunnel and the aerodynamic forces and moment were measured with a Multi-Axis Load Cell JR3. The principal aerodynamic coefficients of compound wing and a rectangular wing such as lift coefficient, drag coefficient, lift to drag ratio wing were computed for different ground clearance and angle of attacks. It was found that at low ground clearance the aerodynamic lift and drag coefficients of compound wing resulted in increased efficiency of the wing. For optimal design of compound wing, the effect of design parameter such as the span size of the middle wing and the anhedral angle on performance of wing were investigated. For certain wings when the span of the middle part reduced, the lift to drag ratio of compound wing increased noticeably. As compared with the rectangular wing, compound wing gives lower fuel consumption. The present design of compound wing can be used to increase the ground effect advantages for new generation of WIG crafts.